Sustainability Standards and Global Governance 2020
DOI: 10.1007/978-981-15-3473-7_10
|View full text |Cite
|
Sign up to set email alerts
|

Global and National Food Safety and Quality Standards: Implications and Impacts for Farmers in Thailand and India

Abstract: 1 The standard is based on third-party certification, and farmers are audited by certification bodies accredited by Foodplus GmbH, the GLOBALGAP secretariat. GLOBALGAP is jointly governed by retailers and producers. In 2012, 49 retailers and food services were members of GLOBALGAP and 197 producers and suppliers. Of the latter, 32 came from developing countries (GLOBALGAP, 2012).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…In India, vegetable production is dominated by small-scale producers, categorized as farmers holding less than 2 hectares of irrigated land [20]. However, small-scale producers have limited nancial and technical support to market fresh produce with high-quality standards [21]. Due to the perishable nature of produce and limited cold storage facilities, small-scale farmers primarily sell fresh vegetables directly to consumers on the roadside or farmers' markets, where sanitary and hygiene conditions are poor [22].…”
Section: Discussionmentioning
confidence: 99%
“…In India, vegetable production is dominated by small-scale producers, categorized as farmers holding less than 2 hectares of irrigated land [20]. However, small-scale producers have limited nancial and technical support to market fresh produce with high-quality standards [21]. Due to the perishable nature of produce and limited cold storage facilities, small-scale farmers primarily sell fresh vegetables directly to consumers on the roadside or farmers' markets, where sanitary and hygiene conditions are poor [22].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research indicates that the adherence to minimum food safety and quality standards and their impact on export potential present numerous challenges and obstacles for farmers. As highlighted by Holzapfel & Hampel‐Milagrosa (2020), most small‐scale farmers primarily cater to local or low‐value export markets, where adherence to private standards is not deemed necessary. Moreover, the poorest segment of small‐scale farmers has not experienced significant benefits from interventions by external donors.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The past literature on smallholder farmers highlight various challenges and barriers in adopting minimum food safety and quality standards and their impact on export potential. Holzapfel & Hampel‐Milagrosa (2020) found that the poorest segment of smallholder farmers has not benefited from donor interventions, and most smallholder farmers serve domestic markets or lower‐value export markets, where private standards are not required. Moreover, the high cost of adopting quality and food safety systems is one of the most critical barriers to adoption (Barbancho‐Maya & López‐Toro, 2022).…”
Section: Introductionmentioning
confidence: 99%